New Finds of Fine Art Objects from the Ananyino Cultural and Historical Area in the Middle Kama Region - Elizaveta M. Chernykh; Alexander E. Mitryakov (Археология евразийских степей, 2022)
The authors publish information about the new art casting finds of the second half of the 1st millennium BC, which are made of copper alloys. The items are of considerable interest as original examples of the artistic work of the population of the Kama Region in the early Iron Age, and as sources allowing to solve the issues of intercultural contacts, the interaction of realms with various economic dominants. Some of the published finds are to a certain extent related to sites whose purpose in the Kama archaeology remains to be studied (Galanovo worship place), and the new discovery of a “Pinezhsky” type of axe allows us to turn back to the issues of the status of individual items, and the sociology of the Early Iron Age societies of the forest zone.